Proceedings of the 4th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle 2007
DOI: 10.17077/drivingassessment.1251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Driver Brake Reaction Times to Multimodal Rear-end Collision Warnings

Abstract: Summary: This study examined the effectiveness of rear-end collision warnings presented in different sensory modalities as a function of warning timing in a driving simulator. Drivers experienced four warning conditions: no warning, visual, auditory, and tactile. The warnings activated when the time-to-collision (TTC) reached a critical value of 3.0 or 5.0 s TTC. Driver reaction time (RT) was captured from the time the driver crossed the warning activation threshold to brake initiation. Mean driver RT data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Wickens' Multiple Resource Theory suggests that, because watching the Icon Sign and watching the road required visual resources, these two activities compete for the same cognitive resources (Wickens et al, 2004). Other research has also found that haptic interfaces can be effective at getting a user's attention (Ho, Reed, & Spence 2006; Ho, Spence, & Tan 2005; Ho, Tan & Spence, 2005; Lee, Hoffman, & Hayes, 2004; Lee, Stoner, & Marshall, 2004; Scott & Gray, 2007); thus, drivers may have paid more attention to the haptic warnings than the visual warnings. Additionally, the position of the Icon Sign may have exacerbated the effect: When using the Icon Sign, drivers may have been looking back and forth to double‐check both the traffic and the sign, because they could not view both at once (this “glancing back and forth” was observed for at least some of the drivers, but was not logged as the experimenter was not watching for this specifically).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wickens' Multiple Resource Theory suggests that, because watching the Icon Sign and watching the road required visual resources, these two activities compete for the same cognitive resources (Wickens et al, 2004). Other research has also found that haptic interfaces can be effective at getting a user's attention (Ho, Reed, & Spence 2006; Ho, Spence, & Tan 2005; Ho, Tan & Spence, 2005; Lee, Hoffman, & Hayes, 2004; Lee, Stoner, & Marshall, 2004; Scott & Gray, 2007); thus, drivers may have paid more attention to the haptic warnings than the visual warnings. Additionally, the position of the Icon Sign may have exacerbated the effect: When using the Icon Sign, drivers may have been looking back and forth to double‐check both the traffic and the sign, because they could not view both at once (this “glancing back and forth” was observed for at least some of the drivers, but was not logged as the experimenter was not watching for this specifically).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exploring visual systems, we chose to explore haptic warning systems because they may be effective in getting the driver's attention in a noisy environment, without requiring the driver to take his or her eyes off the road. A number of research studies have shown that haptic systems have the potential to effectively convey warning information to drivers (Ho, Reed, & Spence 2006; Ho, Spence, & Tan 2005; Ho, Tan, & Spence, 2005; Lee, Hoffman, & Hayes, 2004; Lee, Stoner, & Marshall, 2004; Scott & Gray, 2007). These studies show that haptic warnings can be intuitively associated with direction and result in faster reaction times, especially for braking.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research studies have shown that haptic systems have the potential to effectively convey warning information to drivers. (Scott & Gray, 2007;Ho, Reed & Spence 2006;Lee, Hoffman & Hayes, 2004;Lee, Stoner & Marshall, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The task of gap selection at thru-stop intersections would seem to be safety-critical enough to fall into the "safety issues" category. Scott and Gray (2007) compared reaction times for auditory, visual, and tactile rear-end collision warnings, and found the tactile warning significantly outperformed the visual warning. Results from Scott and Gray (2008) were similar, with the tactile warnings having the shortest mean reaction time, which was significantly shorter than having no warning or having visual warnings.…”
Section: Tactile Displays Literaturementioning
confidence: 99%
“…In the work presented in this report, we explore whether the efficacy of such warnings can be improved by moving the warning system inside the vehicle, allowing different and possibly more convenient positioning of the a visual display so that drivers can see it more easily while also watching traffic, and making other warning modalities possible such as haptic and auditory warnings. Haptic warnings (delivered through vibrating devices) are of particular interest in our studies because they allow drivers to keep their eyes on the road while attending to warnings, and the literature suggests that they can result in faster reaction times than visual or auditory warnings in front-end collision avoidance (Ho, et al 2004;2005;Scott and Gray, 2007;Brown 2005. We report on a series of studies aimed at addressing the research question: can a haptic warning system inside the vehicle provide more safety benefits at a rural thru-stop intersection than can a visual sign placed in the intersection? We asked this question so that we could determine whether it was worth while spending investing more time and energy in haptic warning interfaces; thus these studies are primarily formative in their goals.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%